2008
DOI: 10.4028/www.scientific.net/kem.400-402.227
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for Corrosion Penetration Depth at Cover Cracking in RC Structures

Abstract: Corrosion products which occupy much greater volume accumulate, and generate expansive pressures on the surrounding concrete. The pressure builds up and eventually leads to the cover cracking of the structures. The cracking accelerates further corrosion and leads to the loss of the bond strength and the load carrying capacity. Corrosion cracking would reveal the reducing of the residual service life of the corrosion-affected structures. In this paper, an analytical model is proposed to predict the critical cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Factor analysis results indicated that the regression formula considering the critical radial displacement, concrete strength, cover thickness, and rebar diameter could be obtained using multiple logistic regression analyses. The regression model was established using the fitting function of Equation (16), as given in Equation (17).…”
Section: (3) Regression Analysis Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Factor analysis results indicated that the regression formula considering the critical radial displacement, concrete strength, cover thickness, and rebar diameter could be obtained using multiple logistic regression analyses. The regression model was established using the fitting function of Equation (16), as given in Equation (17).…”
Section: (3) Regression Analysis Datamentioning
confidence: 99%
“…Thus, the relationship between the corrosion rate of the steel reinforcement and the cover thickness was established by determining the point at which the concrete surface of the protective layer cracks. Song et al [16] investigated the corrosion rate of rust expansion cracking on admixture concrete using accelerated corrosion tests under an electric field. They established a mathematical model to describe the steel corrosion rate in the case of a concrete protective layer under different environmental conditions, with consideration of the similarity between rapid electrochemical corrosion and the natural corrosion process.…”
Section: Introductionmentioning
confidence: 99%